Fracture analysis, hydrothermal mineralization and fluid pathways in the Neogene Geitafell central volcano: insights for the Krafla active geothermal system, Iceland - Liotta, Domenico; Brogi, Andrea; Ruggieri, Giovanni; Rimondi, Valentina; Zucchi, Martina; Helgadóttir, Helga Margrét; Montegrossi, Giordano; Friðleifsson, Guðmundur Ómar (Journal of Volcanology and Geothermal Research, 2018)
Studies on hydrothermal fluids circulation and tectonic structures improve the geothermal exploration and exploitation in Iceland. In this paper we present the results of an integrated study (structural, kinematic, fluid inclusions analyses) carried out on a fossil and exhumed geothermal system at Geitafell (SE Iceland), considered an analogue of the active Krafla geothermal system (NE Iceland). Our work is addressed to the relationships between the main structures and the paleo-geothermal fluids circulation at the boundary between the magma chamber (with magma of gabbroic composition) and host rocks, with the aim to get information on those factors having controlled the hydrothermal fluids flow, its storage and the rocks-fluid interaction, at 1–2 km crustal depth. The structural study is mostly based on defining the architecture of mineralized brittle shear zones, where, by measuring length and width of mineralized fractures, permeability was computed in 1.3 × 10−14 m2. As regards the hydrothermal paleo-fluids, fluid inclusions in hydrothermal quartz and calcite, usually associated with epidote and chlorite (i.e., the typical alteration minerals found in Icelandic geothermal fields), recorded a fluid circulation with temperature ranging from about 255 °C to 320 °C, and boiling at the highest temperature. Transient pressure drop, likely related to fracture opening and propagation during tectonic activity, triggered local boiling process testified by fluid inclusions in a calcite sample. During a late evolution the system progressively cooled down to 60–90 °C. Paleo-geothermal fluids were characterized by low-salinity meteoric water, although higher salinity fluids (up to 10.6 wt% NaCl equiv.) entered in the system and mixed with meteoric fluid. In the end, based on results from fluid inclusions, derived fluid density, permeability values and modeling of viscosity, hydraulic conductivity between 2.8 × 10−8 to 1.8 × 10−7 m/s, was also computed within the fluids-channelling brittle shear zones. We finally encourage ...